2000
DOI: 10.2166/wqrj.2000.034
|View full text |Cite
|
Sign up to set email alerts
|

Local impacts of coal mines and power plants across Canada. I. Thallium in waters and sediments

Abstract: A Canada-wide survey was undertaken of sites associated with coal mines and coal-fired electrical generating stations. Several water samples were found to contain very high concentrations of thallium, iron and manganese. High thallium concentrations were found in several sites in Eastern Canada, in spite of the greater coal consumption and production in the western and central regions. The data suggest that coal type (rather than quantity) and/or regional geological contributions are responsible for the high T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…All samples were preserved with 0.2% ultrapure nitric acid. Detailed samplings have been reported (Cheam et al 1995(Cheam et al , 1998(Cheam et al , 2000.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All samples were preserved with 0.2% ultrapure nitric acid. Detailed samplings have been reported (Cheam et al 1995(Cheam et al , 1998(Cheam et al , 2000.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that thallium concentration was higher in streams receiving wastewater and runoff from certain mines, mills, or smelters processing copper-, lead-and zinc-bearing materials than upstream or downstream concentrations. Cheam et al (2000) also found that ninety-five percent of the time, the upstream concentra-tions of thallium and other metals were smaller than downstream, discharge or cooling ponds of the coal mine and power plant operations across Canada. Gold tailings and concentrates are known to contain very high or very low concentrations of thallium.…”
Section: Metal Smelting and Refiningmentioning
confidence: 95%
See 1 more Smart Citation
“…Based mainly on the work of Lin and Nriagu (1999) and Cheam et al (2000Cheam et al ( , 2001. Rehkämper and Nielsen (2004) estimated that pristine rivers have a global mean dissolved Tl content of 7 Ϯ 3 ng/kg.…”
Section: Dissolved Riverine Tl Concentrationsmentioning
confidence: 99%
“…Surfaceand ground-water may be impacted by Tl leaching from naturally occurring mineralized zones; stream concentrations above 2 lg/L have been observed in areas of sulfidic deposits (Xiao et al 2003). A survey of coal mine and power plant sites in Canada reported Tl concentrations \2 lg/L (Cheam et al 2000). However, the discharge from an ash lagoon at a coal power plant in Nova Scotia contained up to 24 lg/L of Tl.…”
Section: Introduction Thallium In the Environmentmentioning
confidence: 99%